Green synthesis of glycerol carbonate by transesterification of bio glycerol with dimethyl carbonate over Mg/ZnO: A highly efficient heterogeneous catalyst - Pradhan G.; Sharma Y.C. (My University, 2025)
Glycerol carbonate is one of the trending value added chemicals in biodiesel industry, which extensively used in pharmaceutical, cosmetic and food industries as well as green solvent in chemical industries. Depending upon the tremendous application of glycerol carbonate the synthesis of such compound from glycerol as by-product of biodiesel is the main focus of the researchers now a days. In this work, highly efficient heterogeneous Mg/ZnO base catalyst was designed through wet impregnation technique and used for transesterification of glycerol with dimethyl carbonate to produce glycerol carbonate. The synthesized catalysts were characterized by XRD, SEM -EDX, FT-IR, TGA-DSC, BET analyzer and XPS to find out the physico-chemical properties of catalyst. The conversion and validation of glycerol carbonate synthesis was confirmed by 1H and 13C NMR spectroscopy and gas chromatography also. It was observed at 80 °C the conversion of glycerol and GLC yield were to be obtained 98.4%, 96.57% respectively for the catalyst in 2 h time period. Finally, all the reaction parameters like temperature, molar ratio of DMC/Glycerol, catalyst loading, reaction time were optimized and the respective effects were examined. © 2020 Elsevier Ltd